Multisource Thermal Model Describing Transverse Momentum Spectra of Final-State Particles in High-Energy Collisions - Liu, Fu-Hu; Chen, Jia-Yu; Zhang, Qiang (Advances in High Energy Physics, 2022)
In this minireview article, the transverse momentum spectra of final-state particles produced in high-energy hadron-hadron, hadron-nucleus, and nucleus-nucleus collisions described by the multisource thermal model at the quark or parton level are summarized. In the model, the participant or contributor quarks or partons are considered to contribute together to the transverse momentum distribution of final-state particles with different modes of contributions. The concrete mode of contribution is generally determined by the difference of azimuthal angles of contributor partons in their emissions.